Index 1 fixed points of orientation reversing planar homeomorphisms
Let \(U R^2\) be an open subset, \(fU → f(U) R^2\) be an orientation reversing homeomorphism and let \(0 U\) be an isolated, as a periodic orbit, fixed point. The main theorem of this paper says that if the fixed point indices \(i_R^2